If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4t + -54 = 3t + -9 Reorder the terms: -54 + 4t = 3t + -9 Reorder the terms: -54 + 4t = -9 + 3t Solving -54 + 4t = -9 + 3t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-3t' to each side of the equation. -54 + 4t + -3t = -9 + 3t + -3t Combine like terms: 4t + -3t = 1t -54 + 1t = -9 + 3t + -3t Combine like terms: 3t + -3t = 0 -54 + 1t = -9 + 0 -54 + 1t = -9 Add '54' to each side of the equation. -54 + 54 + 1t = -9 + 54 Combine like terms: -54 + 54 = 0 0 + 1t = -9 + 54 1t = -9 + 54 Combine like terms: -9 + 54 = 45 1t = 45 Divide each side by '1'. t = 45 Simplifying t = 45
| 2n+6=48-5n | | -7n+10n=-33 | | (2(x^(1/2)))^2 | | 5t-92=t | | 1+7x+3x=21 | | 4p-32=p+31 | | 3m+5n=7 | | y=4y-30 | | -1=x-6+5 | | 2m=n-4 | | 21=4v-7v | | 9b-22=7b-16 | | -2(1-6r)=-2+4r | | 4v+6=41-3v | | 4s+14=2s+66 | | 3x^2+6x=168 | | p+p+64=180 | | -3(x-1)=-2x-3 | | 2a-21=a | | 12x-11y=23 | | 3/13=u/10 | | 5(2x+5)-1=-2x | | 2b-48+2b-96=180 | | 3u-64=u | | 10y+9=13y+3 | | 3n+4(5n+2)=8+3n | | 16z-21+2z+39=180 | | -3(1-5m)+4=1-2m | | 7=an-1+-15 | | 4c-65=5c-85 | | 4c-65=5c-68 | | -2+3p=6p-4-2p |